2016
DOI: 10.1007/s00430-016-0464-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an echovirus 18 outbreak in Thuringia, Germany: insights into the molecular epidemiology and evolution of several enterovirus species B members

Abstract: In October and November 2010, six children and one woman were presented with symptoms of aseptic meningitis in Jena, Thuringia, Germany. Enterovirus RNA was detected in the cerebrospinal fluid of all patients by RT-PCR, and preliminary molecular typing revealed echovirus 18 (E-18) as causative agent. Virus isolates were obtained from stool samples of three patients and several contact persons. Again, most isolates were typed as E-18. In addition, coxsackievirus B5 (CV-B5) and echovirus 25 (E-25) were found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…E18, which was detected at low prevalence in mainland China in previous studies, became the predominant EV serotype causing VE and VM in Hebei province in 2015 . The E18 serotype of EV‐B has caused many outbreaks of aseptic meningitis in the USA, Japan, Germany, and other regions . Prior to our study, E18 had been detected sporadically and was rarely reported in mainland China .…”
Section: Discussionmentioning
confidence: 52%
“…E18, which was detected at low prevalence in mainland China in previous studies, became the predominant EV serotype causing VE and VM in Hebei province in 2015 . The E18 serotype of EV‐B has caused many outbreaks of aseptic meningitis in the USA, Japan, Germany, and other regions . Prior to our study, E18 had been detected sporadically and was rarely reported in mainland China .…”
Section: Discussionmentioning
confidence: 52%
“…However, it is unclear whether the recombination of SVDV occurred in humans or pigs 29 . In addition, the non-structural protein and un-translated regions, which have diverse functions in the viral replication are characterized by species-specific 11 . Recombination events usually occur in non-structural regions of EV-B 23, 3032 , which is consistent with our report.…”
Section: Discussionmentioning
confidence: 99%
“…Non-polio human enteroviruses (EVs), especially the species Enterovirus B (EV-B), are major causative agents of these diseases. Echovirus 18 (E18), a serotype of EV-B, has mostly been reported as an important pathogen that has caused many outbreaks of aseptic meningitis in the United States, 1 , 2 Japan, 3 Korea, 4 Germany, 5 and other countries or regions. 6 So far, there has been no report of an E18-associated encephalitis/meningitis outbreak in mainland China, but little E18 epidemiological data is available.…”
mentioning
confidence: 99%